Teacher Development Program in Efforts to Improve the Effectiveness of Technology-Based Islamic Education: An Exploratory Sequential Design - Sabariah, Sabariah; Hartono, Hartono; Suhari, Suhari; Muhammad, Mazni Binti; Anugraha, Krisna Murti (STAI Publisistik Thawalib Jakarta, 2026)
The research problem in this study is that the development of Islamic Education teachers has not yet been optimal in integrating technology, resulting in low learning effectiveness and limited digital competence. The purpose of this study is to analyze teacher development and the influence of technology on the effectiveness of Islamic Education learning, and to formulate an effective development model. The research used an exploratory sequential design: a qualitative case study with 15 teachers (interviews, observations, and documentation), followed by a quantitative correlational stage with 50 students (Likert-scale questionnaires analyzed with SPSS). The results show that technology-based teacher development has a significant effect on the effectiveness of Islamic Education learning. Qualitatively, teachers experienced improvements in lesson planning, the use of varied teaching methods, and the utilization of digital media such as videos, applications, and online learning platforms, making learning more interactive, engaging, and student-centered. Quantitatively, instructional development (X1) contributed 47.4%, technology-based value-added development (X2) contributed 57.4%, and simultaneously, both contributed 59.6% to learning outcomes. The data were tested for normality and found to be valid and reliable. The study concludes that technology-based teacher development significantly and measurably improves the effectiveness of Islamic Education instruction. The significance of this research lies in producing a technology-based teacher development model as a foundation for policy development and modern Islamic education training.